Pengaruh tekanan waktu, tindakan supervisi, risiko audit, locus of control dan komitmen profesional terhadap penghentian prematur atas prosedur audit (studi empiris pada KAP di Jawa Tengah dan DIY) - Kusumaningrum, febriana (2016)
This research aimed to analyze the influence of time pressure, supervision, audit risk, locus of control and professional commitment to premature sign-off of audit procedure. This research was a quantitative one. Data were collected through a survey by using questionnaires. The population of this research are all auditors working on the CPA's in Jawa Tengah and DIY. The sample of this research are 51 auditors working on the CPA's in Jawa Tengah and DIY. Determination of samples by using purposive sampling method. The analysis method of this research using multiple regression analysis assisted with SPSS 17. The result of this research indicate that time pressure, audit risk, and professional commitment affected the premature sign-off of audit procedure, while supervision and locus of control has no effect to the premature sign-off of audit procedure.